Reminiscences - Hadkins, Albert Abraham Randolph St Clair, 1834-1911. (1892)
Reminiscences of life in gold-rush era.
Transcript.
Manuscript reference no. : NLA MS 8849.
Small businessman.
Keywords: Hadkins, Albert Abraham Randolph St Clair, -- 1834-1911.; Immigrants -- Australia -- Biography; Small business -- Australia